Meningkatkan Kualitas Dan Produktivitas Unformed Plate Pada Proses Pasting Battery Di PT. XYZ - Kinantaka, Rizky Budiyasa; Romli, Ikhsan (JURNAL TEKNIK INDUSTRI, 2021)
This research raises the title of increasing the quality and productivity of the unformed plate in the pasting battery process at PT.XYZ. Unformed plate is a grid that has been coated with paste and processed pasting. The quality of the unformed plate can affect the power quality and lifespan of the battery. Unformed plate can be perforated caused by mold on the plate. a paster machine that has shifted due to lack of maintenance and broken grids from castings that have passed the quality check. This study aims to increase the productivity and quality of unformed plates in the pasting process. The research method for data collection uses observation, interviews, and experience. The data analysis research used is the six sigma method which includes define, analyze and improve. Repair and maintenance actions are the foundation of the strength of quality improvement. productivity increases. The results of the research analysis of improving the quality and productivity of the unformed plate in the pasting process are reduced rejects of the unformed plate and an increase in the quality of the resulting battery. Actions taken are repairs and maintenance using the six sigma method. For the reject pasting graph per month has decreased.